2013
DOI: 10.1016/j.jviromet.2013.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Antibody inhibition of human cytomegalovirus spread in epithelial cell cultures

Abstract: Anti-cytomegalovirus (CMV) antibodies reduce the incidence of CMV transmission and ameliorate the severity of CMV-associated disease. Neutralizing activity, measured as the ability of antibodies to prevent entry of cell-free virus, is an important component of natural immunity. However, in vivo CMV amplification may occur mainly via spread between adjacent cells within tissues. Thus, inhibition of cell-to-cell spread may be important when evaluating therapeutic antibodies or humoral responses to infection or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 46 publications
(97 reference statements)
0
37
1
Order By: Relevance
“…However, just as viral entry is cell type specific, the mechanisms of cell-to-cell spread may also differ between cell types. Several studies suggest that cell-to-cell spread of CMV in endothelial cell cultures is sensitive to antibody inhibition (34,39,46,47), while we and others have shown that antibodies can limit the spread of CMV in epithelial cell cultures (48)(49)(50).…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…However, just as viral entry is cell type specific, the mechanisms of cell-to-cell spread may also differ between cell types. Several studies suggest that cell-to-cell spread of CMV in endothelial cell cultures is sensitive to antibody inhibition (34,39,46,47), while we and others have shown that antibodies can limit the spread of CMV in epithelial cell cultures (48)(49)(50).…”
mentioning
confidence: 68%
“…CMV spread in epithelial cells involves gB, gH, and the pentamer, and antibody inhibition of spread closely correlates with neutralizing activity. In a recent study, we showed that HIG or sera from naturally infected subjects can restrict CMV spread in epithelial cell cultures (48). To identify viral factors involved in epithelial cell spread and to determine whether any of our antibodies were discordant with respect to inhibition of epithelial cell entry versus spread, each was assayed for epithelial cell entryneutralizing activity and spread inhibition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies directed to CMV limit cell-to-cell spread in endothelial cells (180)(181)(182) and epithelial cells (183), as evidenced by a lack of focal spread in the presence of CMV-neutralizing antibodies, although virus strains may exhibit various degrees of sensitivity. Cell-to-cell spread in fibroblasts, in contrast, may proceed through transient microfusion events (173) and are largely insensitive to antibody-mediated inhibition (138,163,180,(183)(184)(185).…”
Section: Cell-to-cell Spread Avoids Antibody-mediated Inhibitionmentioning
confidence: 99%
“…Cell-to-cell spread in fibroblasts, in contrast, may proceed through transient microfusion events (173) and are largely insensitive to antibody-mediated inhibition (138,163,180,(183)(184)(185). Given the cell-type-specific mechanisms of CMV entry, it is not surprising that the virus exhibits cell-type-dependent mechanisms of cell-to-cell spread.…”
Section: Cell-to-cell Spread Avoids Antibody-mediated Inhibitionmentioning
confidence: 99%